2017
DOI: 10.1002/jso.24809
|View full text |Cite
|
Sign up to set email alerts
|

A study of 853 high grade osteosarcomas from a single institutionAre outcomes in Indian patients different?

Abstract: Our patients appeared to have poorer survival compared to most Western data, possibly attributable to large tumors. In contrast to existing data, males (71%) were predominantly affected and only patients with 100% necrosis qualified as good responders regarding OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 38 publications
3
28
1
Order By: Relevance
“…This, the largest documented series of stand‐alone intercalary ECRT grafts for primary extremity high grade diaphyseal tumors has demonstrated comparable local control and survival compared to other series using alternative methods of reconstruction . Our own series of 520 non metastatic osteosarcomas treated with limb salvage surgery (excluding ECRT) had a similar local recurrence rate of 10% . In the series by Mavrogenis et al 8% (12 of 151) of osteosarcomas reconstructed with a megaprosthesis had local recurrence while Zhang et al documented 9% (10 of 108) local recurrence in their study of megaprostheses for high‐grade osteosarcoma around the knee.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…This, the largest documented series of stand‐alone intercalary ECRT grafts for primary extremity high grade diaphyseal tumors has demonstrated comparable local control and survival compared to other series using alternative methods of reconstruction . Our own series of 520 non metastatic osteosarcomas treated with limb salvage surgery (excluding ECRT) had a similar local recurrence rate of 10% . In the series by Mavrogenis et al 8% (12 of 151) of osteosarcomas reconstructed with a megaprosthesis had local recurrence while Zhang et al documented 9% (10 of 108) local recurrence in their study of megaprostheses for high‐grade osteosarcoma around the knee.…”
Section: Discussionmentioning
confidence: 50%
“…There were 53 male and 17 female patients with a mean age of 17 years (range 1-36 years). The femur was the most commonly involved bone (46) followed by tibia (17), humerus (6), and ulna (1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients were nonmetastatic at presentation. ey received neoadjuvant and adjuvant chemotherapy as per the existing hospital protocol [7]. Sixty one of 720(8.4%) patients had diaphyseal disease.…”
Section: Patientsmentioning
confidence: 99%
“…While the survival factors associated with metastatic osteosarcoma are complex and controversial, surgical resection is widely accepted as a beneficial treatment method. Some retrospective studies have reported the benefits of primary tumour resection (PTR) and primary tumour and metastatic site resection (PTMR) [7][8][9]. In general, surgical resection, combined with chemotherapy, has been shown to result in better prognosis [10,11].…”
Section: Introductionmentioning
confidence: 99%